The delivery of compassionate nursing care in a tick-box culture: Qualitative perspectives from a realist evaluation of intentional rounding. (July 2020) - Sims, Sarah; Leamy, Mary; Levenson, Ros; Brearley, Sally; Ross, Fiona; Harris, Ruth
Abstract: Background: Compassion is integral to professional nursing practice worldwide and a fundamental value in healthcare. Following serious care failures at a healthcare provider in the United Kingdom, a government commissioned report (the Francis Report) made several recommendations for strengthening compassion in nursing care and consequently 'intentional rounding' was incorporated into nursing practice in the United Kingdom. Intentional rounding is a structured process implemented primarily in the United Kingdom, North America and Australia, whereby nurses conduct 1–2 hourly checks on every patient using a standardised protocol and documentation. Objectives: To examine the role of intentional rounding in the delivery of compassionate nursing care in England from multiple perspectives. Methods: This paper reports qualitative findings from one phase of a realist evaluation of intentional rounding which used a mixed-methods approach. Individual, semi-structured interviews were undertaken with 33 nursing staff, 17 senior nurse managers, 34 patients and 28 family carers from three geographically spread case study hospital sites in England. Interviews elicited detailed reflections on the contexts, mechanisms and outcomes of intentional rounding and how it impacted the interviewee and those around them. Results: This study found little evidence that intentional rounding ensures the comfort, safety or dignity of patients or increases the delivery of compassionate care. The systematised approach of intentional rounding emphasises transactional care delivery in the utilisation of prescribed methods of recording or tick boxes rather than relational, individualised patient care. It has the potential to reduce the scope of nursing care to a minimum standard, leading to a focus on the fundamentals as well as the prevention of adverse events. Its documentation is primarily valued by nursing staff as a means of protecting themselves through written proof or 'evidence' of care delivered, rather than as a means of increasing compassionate care. Conclusions: This large-scale, theoretically-driven study of intentional rounding – the first of its kind – demonstrates that intentional rounding prioritises data collection through tick boxes or a prescriptive and structured recording of care. Thus, intentional rounding neither improves the delivery of compassionate nursing care nor addresses the policy imperative it was intended to target. This study raises questions about the role, contribution and outcomes from intentional rounding and suggests a need for a wider, international debate within the nursing profession about its future use. If an intervention to increase compassionate nursing care is required, it may be better to start afresh, rather than attempting to adapt the system currently implemented.